Optimizing Performance: A Dynamic Analysis of Credit Quality, Operational Efficiency, and Their Influence on ROA in Indonesian Islamic Banks - Munadiati, Munadiati; Muhammad, Alfian; Yahya, M.; Wulandari, Putri (Jihbiz: Global Journal of Islamic Banking and Finance, 2025)
ABSTRACT This study investigates the influence of key financial management strategies on the Return on Assets (ROA) of Islamic Commercial Banks (ICBs) in Indonesia. The analysis explores the direct and indirect effects of Funding Deposit Ratio (FDR) and Non-Performing Financing (NPF) on ROA, with Operational Costs to Operational Income (BOPO) as a mediating variable. The findings reveal a significant influence of FDR on ICB performance. While a higher FDR leads to lower operational costs, it might also be associated with lower profitability due to deposit interest rates. ICBs need to strike a balance between cost-effective deposits and exploring alternative funding sources. While the direct effect of NPF on ROA is unclear, it significantly impacts profitability indirectly through its influence on operational efficiency. Higher NPF levels can lead to increased costs, potentially reducing ROA. Therefore, effective NPF management is crucial for ICBs. The study further emphasizes the importance of managing operational efficiency (BOPO). Lower BOPO, indicating efficient use of operational income, is directly linked to a higher ROA. ICBs should focus on cost-saving measures and optimizing operational processes to improve efficiency and maximize ROA. Overall, the research highlights the critical role of a holistic approach to financial management in ICBs. By effectively managing FDR, NPF, and BOPO, ICBs can achieve a well-balanced funding structure, minimize bad debt risk, and optimize operational efficiency. Keywords: Islamic Banking, Performance, Credit Quality, Operational Efficiency, and Return on Assets.